Myocarditis associated with influenza infection in five children. Issue 5 (September 2018) - Aykac, Kubra; Ozsurekci, Yasemin; Kahyaoglu, Pinar; Basaranoglu, Sevgen T.; Ertugrul, Ilker; Alp, Alpaslan; Cengiz, Ali B.; Kara, Ates; Ceyhan, Mehmet
Abstract: Background: Myocarditis is an inflammatory condition located mainly in the myocardium. It is caused by a variety of bacterial and viral infections. Influenza is one of the most common relevant viruses that cause myocarditis. Objectives: We attempted to share our experiences about clinical and laboratory findings, cardiac evaluation, and treatment of children with influenza myocarditis. Methods: This retrospective study was performed by the Department of Pediatric Infectious Diseases at the Faculty of Medicine, Hacettepe University in Turkey. The medical records of patients diagnosed with myocarditis associated with an influenza infection between January 2014 and January 2017 were systematically reviewed. Results: Vaccination seems likely to be an important protection strategy for both influenza infections and complications.